Genome-wide association with footrot in hair and wool sheep - Cinar, Mehmet Ulas; Oliveira, Ryan D.; Hadfield, Tracy S.; Lichtenwalner, Anne; Brzozowski, Richard J.; Settlemire, C. Thomas; Schoenian, Susan G.; Parker, Charles; Neibergs, Holly L.; Cockett, Noelle E.; White, Stephen N. (Frontiers in Genetics, 2024)
Ovine footrot is an infectious disease with important contributions from Dichelobacter nodosus and Fusobacterium necrophorum. Footrot is characterized by separation of the hoof from underlying tissue, and this causes severe lameness that negatively impacts animal well-being, growth, and profitability. Large economic losses result from lost production as well as treatment costs, and improved genetic tools to address footrot are a valuable long-term goal. Prior genetic studies had examined European wool sheep, but hair sheep breeds such as Katahdin and Blackbelly have been reported to have increased resistance to footrot, as well as to intestinal parasites. Thus, footrot condition scores were collected from 251 U.S. sheep including Katahdin, Blackbelly, and European-influenced crossbred sheep with direct and imputed genotypes at OvineHD array (>500,000 SNP) density. Genome-wide association was performed with a mixed model accounting for farm and principal components derived from animal genotypes, as well as a random term for the genomic relationship matrix. We identified three genome-wide significant associations, including SNPs in or near GBP6 and TCHH. We also identified 33 additional associated SNPs with genome-wide suggestive evidence, including a cluster of 6 SNPs in a peak near the genome-wide significance threshold located near the glutamine transporter gene SLC38A1. These findings suggest genetic susceptibility to footrot may be influenced by genes involved in divergent biological processes such as immune responses, nutrient availability, and hoof growth and integrity. This is the first genome-wide study to investigate susceptibility to footrot by including hair sheep and also the first study of any kind to identify multiple genome-wide significant associations with ovine footrot. These results provide a foundation for developing genetic tests for marker-assisted selection to improve resistance to ovine footrot once additional steps like fine mapping and validation are complete.